1999
DOI: 10.1046/j.1365-313x.1999.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of plastid psbA, rbcL and rpl32 UTR elements by chloroplast transformation: tobacco plastid gene expression is controlled by modulation of transcript levels and translation efficiency

Abstract: In vivo analysis of plastid psbA, rbcL and rpl32 UTR elements by chloroplast transformation: tobacco plastid gene expression is controlled by modulation of transcript levels and translation ef®ciency Texas A&M University, College Station, Texas, USA Summary 5¢ and 3¢ untranslated regions (UTRs) of plastid RNAs act as regulatory elements for post-transcriptional control of gene expression. Polyethylene glycol-mediated plastid transformation with UTR±GUS reporter gene fusions was used to study the function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
4
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 70 publications
(99 reference statements)
8
125
4
2
Order By: Relevance
“…It has previously been shown that genes under the control of the psbA promoter/5#UTR achieve very high levels of expression (Fernandez San-Millan et al, 2003;Dhingra et al, 2004;Watson et al, 2004). The 5#UTR has been hypothesized to enhance translation of proteins under its control (Eibl et al, 1999). The aadA gene confers spectinomycin resistance for selection of transformed shoots (GoldschmidtClermont, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that genes under the control of the psbA promoter/5#UTR achieve very high levels of expression (Fernandez San-Millan et al, 2003;Dhingra et al, 2004;Watson et al, 2004). The 5#UTR has been hypothesized to enhance translation of proteins under its control (Eibl et al, 1999). The aadA gene confers spectinomycin resistance for selection of transformed shoots (GoldschmidtClermont, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Because reporter protein levels do not always correlate with steady-state transcript abundance, it is evident that translation is a crucial control step for optimizing protein production. Several studies have revealed a minimal effect of 3′UTR sequences on chloroplast gene translation [42] although, recently, the petD 3′UTR was shown to influence reporter protein expression [43]. By contrast, many 5′UTRs mediate enhanced translation of downstream open-reading-frames [44].…”
Section: Optimizing Foreign Gene Expression In Chloroplastsmentioning
confidence: 99%
“…By contrast, many 5′UTRs mediate enhanced translation of downstream open-reading-frames [44]. One of the most effective of these, the tobacco psbA 5′UTR, directs strong, light-regulated, translation of chimeric transcripts regardless of which coding sequence, 3′UTR or promoter it is combined with [42].…”
Section: Optimizing Foreign Gene Expression In Chloroplastsmentioning
confidence: 99%
“…The junction point of the large single-copy region (LSC) and IR-A of the tobacco plastome (Shinozaki et al, 1986) are shown. Gene abbreviations can be found in Table I Staub and Maliga, 1994a;Eibl et al, 1999). However, researchers still routinely used regulatory elements including promoters and untranslated regions with homology to sequences within the host plastome (Verma and Daniell, 2007), often because these were the only sequences readily available for use.…”
Section: Discussionmentioning
confidence: 99%
“…While these expression levels are too high for most metabolic engineering strategies for the production of chemicals, fuels, or materials without creating unwanted stress on the host plant, expression levels can be somewhat controlled by the choice of regulatory elements flanking the transgenes. Plastid gene expression is regulated to a large extent at the posttranscriptional level (Sugita and Sugiura, 1996;Stern et al, 1997;Bruick and Mayfield, 1999;Dubald et al, 2008), and 5# and 3# untranslated regions (UTRs) have been shown to impact translational efficiency and mRNA stability, respectively (Eibl et al, 1999). However, these UTR sequences, as well as any other sequences with significant homology to the host's plastome, must be used with care, since they can cause unwanted rearrangements (Svab and Maliga, 1993;Staub and Maliga, 1994a;Rogalski et al, 2006Rogalski et al, , 2008McCabe et al, 2008;Zhou et al, 2008;Gray et al, 2009).…”
mentioning
confidence: 99%